Instagram Analysis @Cashaofficial As Bean Bag Promotion Media: Analisis Instagram @Cashaofficial sebagai Media Promosi Bean Bag - Mukti, Rindang Putri Kharisma; Rochmaniah, Ainur (Indonesian Journal of Innovation Studies, 2023)
In Indoensia instagram is one of the most popular platform who used by more than a half of population. This because some of it’s several features can support sales promotion activities which considered very crusial . The efficiency of Instagram as a promotional media is considered to have many advantages including ease of use, effective time and effort from both the seller and buyer side, has easy reach so that it can be accessed anywhere and anytime and there is no age discrimination. This study aims to analyze Instagram @Cashaofficial in carrying out promotions for their millennials sofa product, namely bean bags. In this study, researchers used several elements of social media marketing, namely content creation, content sharing, connecting, and community building. This study uses a qualitative descriptive technique. Primary data can be obtained through observations and direct observations of the research object. With the use of good features, @cashaofficial is able to share information that is quite important to other Instagram users, but on the one hand the @cashaofficial team has not used all Instagram features in conducting promotions and there are still some features that are not used as promotional media.